On the Centrality of Information Appraisal in Health Literacy Research - Nicola Diviani (SLACK Incorporated, 2019)
This article aims to make the case for the centrality of, and the lack of attention to, health information appraisal in health literacy research. First, it will be shown that how citizens and patients interact with health information has changed dramatically in the last decades, after the shift toward patient-centered health care and the increase in publicly available health information. Second, it will be argued that although these changes have had a profound effect on how people's interactions with health information should be studied, research has not been able to fully reflect the changes. More specifically, after presenting an example making the case for the centrality of health information appraisal, it will be shown how health literacy research still has a strong focus on its functional component. The main implications of the lack of attention to the dimension of health information appraisal will be discussed and possible future directions to advance health literacy research will be suggested.